1971
DOI: 10.1037/h0030910
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect interference in the recall of paired associates.

Abstract: A series of three experiments was reported in which attention was directed towards an assessment of the interference operating upon forward and backward associations. Evidence was found for direct and indirect interference in four transfer paradigms (A-B, A-D; A-B, C-B; A-B, D-A; and A-B, B-C). Failures of others to find indirect interference were attributed to their use of a high degree of original learning. The difficulty of the principle of associative symmetry to accommodate certain outcomes of the three e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Interference between cues, recently observed in predictive learning studies, had been found much earlier in the verbal learning tradition (Abra, 1967;Cheung & Goulet, 1968;Keppel, Bonge, Strand, & Parker, 1971;Schwartz, 1968). In predictive learning, the evidence for interference between cues comes mainly from human studies (see, for example, Escobar, Pineño, & Matute, 2002;Matute & Pineño, 1998;Pineño, Ortega, & Matute, 2000), though there is also evidence for interference between cues from animal experiments (Escobar, Arcediano, & Miller, 2001;Escobar, Matute, & Miller, 2001;Escobar & Miller, 2003).…”
mentioning
confidence: 91%
“…Interference between cues, recently observed in predictive learning studies, had been found much earlier in the verbal learning tradition (Abra, 1967;Cheung & Goulet, 1968;Keppel, Bonge, Strand, & Parker, 1971;Schwartz, 1968). In predictive learning, the evidence for interference between cues comes mainly from human studies (see, for example, Escobar, Pineño, & Matute, 2002;Matute & Pineño, 1998;Pineño, Ortega, & Matute, 2000), though there is also evidence for interference between cues from animal experiments (Escobar, Arcediano, & Miller, 2001;Escobar, Matute, & Miller, 2001;Escobar & Miller, 2003).…”
mentioning
confidence: 91%
“…It should be noted that this is not the case in the experiments published in the paired-associate learning literature (e.g., Keppel et al, 1971). In these experiments, participants learn many different cue-outcome relationships (e.g., 12 per learning phase in Keppel et al, 1971). Thus, it seems unlikely that inferential reasoning has significantly contributed to these instances of RIBC.…”
Section: Discussionmentioning
confidence: 57%
“…At the bottom (the diamond), the results of the random-effects meta-analysis are shown be particularly favored in experiments in which only a few deterministic relationships are to be learned and participants are under time pressure to respond during the test (e.g., Escobar et al, 2002;Luque et al, 2008;Luque et al, 2010;Luque et al, 2011;Matute & Pineno, 1998a). It should be noted that this is not the case in the experiments published in the paired-associate learning literature (e.g., Keppel et al, 1971). In these experiments, participants learn many different cue-outcome relationships (e.g., 12 per learning phase in Keppel et al, 1971).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations